Contribution of Risk Perception and Communication in Aviation Safety Events. Issue 3 (March 2022) - Chionis, Dimitrios; Karanikas, Nektarios; Iordan, Alice-Rebecca; Svensson-Dianellou, Antonia
Although effective risk management during operations relies on risk perception and risk communication, the aviation industry has not systematically considered the contribution of these two constructs to safety events. This study analyzed a representative sample of safety investigation reports (1) to identify the degree to which risk perception and communication and their factors have been influential overall and across various flight operation stages of investigated events, and (2) to examine whether their contribution has changed with time. The analysis of 140 reports showed environmental factors affected risk communication and perception most frequently, whereas emotional and physiological factors were found in the sample with very low frequencies. Also, risk communication and perception and their factors did not appear with the same frequency across the various flight stages, and a few variations were observed over time. The aviation industry could consider the results of this study to steer its efforts toward mitigating the adverse effects of factors related to ineffective risk perception and communication. This could include the inclusion of respective factors in safety reporting schemes, investigation methods and analyses and, possibly, a tailored approach to the various flight stages and targeted risk literacy interventions.